2018
DOI: 10.5152/tud.2018.78861
|View full text |Cite
|
Sign up to set email alerts
|

Investigating knowledge levels of university students about infertility

Abstract: Objective: The aim of this study was to determine the knowledge levels of university students about infertility and investigate the differences in knowledge levels according to sociodemographic variables and some lifestyle factors. Material and methods:The sample of the study consisted of 9693 undergraduate students (5002 females, 4691 males) from 12 regions. Regions were determined according to Statistical Region Units Classification-1 criteria. Infertility Knowledge Test (IKT) was used as a data collection t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0
5

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(26 citation statements)
references
References 26 publications
1
17
0
5
Order By: Relevance
“…(p <0.05). In the study conducted by Siyez and Siyez, Çalışkan et al, Kaymak et al on sexually transmitted diseases, it was found that training on STD increased the mean score [5,7,12].…”
Section: Xmentioning
confidence: 99%
See 1 more Smart Citation
“…(p <0.05). In the study conducted by Siyez and Siyez, Çalışkan et al, Kaymak et al on sexually transmitted diseases, it was found that training on STD increased the mean score [5,7,12].…”
Section: Xmentioning
confidence: 99%
“…Conditions such as inadequate sexual education programs in developing countries, the age of sexual intercourse in developed and developing countries, having more than one sexual partner, having sexual intercourse for money, not using condoms during sexual intercourse, joint use of tools used for manicure, pedicure, razor , piercing and tattooing, and the use of dental instruments without sterilization are among the risk factors for STI. [5][6][7]. According to the data of the World Health Organization, more than 1 million people are caught with STIs every day in the world.…”
Section: Introductionmentioning
confidence: 99%
“…Angka infertilitas di Indonesia sendiri pada wanita dengan usia reproduktif adalah sebesar 6% (HIFERI, 2013). Meningkatkan pengetahuan pada mahasiswa mengenai infertilitas diyakini dapat mengurangi risiko dan keterlambatan dalam mencari bantuan medis di masa mendatang (Siyez et al, 2018). Penelitian di beberapa negara pada mahasiswa, seperti Denmark (Sørensen et al, 2016), Hongkong (Chan, et al, 2015), Nigeria (Abiodun, et al, 2016), dan Turkey (Siyez et al, 2018), membuktikan bahwa mahasiswa memiliki pengetahuan dan sikap yang kurang baik terhadap perencanaan berkeluarga serta faktor dan terapi infertilitas.Pendidikan kedokteran merupakan salah satu pendidikan tinggi yang memakan waktu cukup lama.…”
Section: Pendahuluanunclassified
“…Sexual health education can be effective in increasing university students' knowledge of infertility. 15 Most women (59%) were aged between 20 to 30 years indicating concern about their fertility and need for evaluation. More than half (63%) women were from the middle socio-economic strata.…”
Section: Introductionmentioning
confidence: 99%